Heat pump for thermal power production in dairy farm - Jordan, Rodrigo A. (2016)
Besides cold for milk cooling, dairy facilities need to produce hot water for cleaning of tools and equipment. Overall, ohmic heating has been used in dairy farms, increasing power consumption and manufacturing costs. Therefore, as an alternative to reduce power consumption, this paper proposed a water-water heat pumping for simultaneous cold and heat generations. Accordingly, operational tests were performed with three heat-pump prototypes designed for dairy farms, in both laboratory and field levels. At laboratory, tests were carried out using electricity and CNG to define a coefficient of performance (COP). Biogas tests were performed in the field to measure its consumption. CNG average consumption was of 1.118 m3/h, while biogas consume was of 2.02 m3/h. COP averages of CNG driven pump were 0.20 for cooling, 0.39 for heating, and 0.59 for global. For electric-power driving, COP values were 1.75 for cooling, 2.25 for heating, and 4.00 for global. In addition to evaporating and compensating temperatures, engine rotation was one factor of influence on heat-pump performance.